2002
DOI: 10.1159/000058450
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Intake of Lactic Acid Bacteria and Risk Reduction of Bladder Cancer

Abstract: Introduction: A kind of lactic acid bacteria, Lactobacillus casei strain Shirota, shows antitumor activity in experimental animals. One clinical trial using L. casei showed a significant decrease in the recurrence of superficial bladder cancer. So, to assess the preventive effect of the intake of L. casei, widely taken as fermented milk products in Japan, against bladder cancer, we conducted a case-control study. Methods: A total of 180 cases (mean age: 67 years, SD 10) were selected from 7 hospitals, and 445 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
88
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(93 citation statements)
references
References 23 publications
0
88
0
5
Order By: Relevance
“…Increasing evidence has also supported the possibility that L. casei strain Shirota can act as an effective immunomodulator in humans. Oral administration of L. casei strain Shirota restored NK cell activity in subjects with relatively low NK cell activity (20,24,25), although it remains to be investigated whether L. casei strain Shirota-mediated recovery of NK cell activity was connected with a reduction in cancer incidence (2,12,27). Previous studies using experimental murine models showed that L. casei strain Shirota could prevent infections of pathogenic bacteria and viruses through the activation of innate immune defenses (10,22) and inhibit the development of allergies, autoimmune diseases, and inflammatory bowel diseases, probably through normalizing dysregulated host immune systems (16,19,21,23,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has also supported the possibility that L. casei strain Shirota can act as an effective immunomodulator in humans. Oral administration of L. casei strain Shirota restored NK cell activity in subjects with relatively low NK cell activity (20,24,25), although it remains to be investigated whether L. casei strain Shirota-mediated recovery of NK cell activity was connected with a reduction in cancer incidence (2,12,27). Previous studies using experimental murine models showed that L. casei strain Shirota could prevent infections of pathogenic bacteria and viruses through the activation of innate immune defenses (10,22) and inhibit the development of allergies, autoimmune diseases, and inflammatory bowel diseases, probably through normalizing dysregulated host immune systems (16,19,21,23,34).…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials revealed that oral ingestion of L. casei strain Shirota prevented the recurrence of superficial bladder cancer and the development of colorectal tumors with moderate or higher atypia (2,12), and an epidemiological survey showed that the habitual intake of fermented milk containing L. casei strain Shirota reduced the risk of bladder cancer (27). Moreover, the intake of fermented milk containing L. casei strain Shirota restored NK cell activity in subjects with relatively low NK cell activity (20,24,25).…”
mentioning
confidence: 99%
“…10) Clinical studies conducted in humans have indicated that LAB can alleviate the symptoms of atopy [11][12][13][14] and perennial allergic rhinitis [15][16][17] and enhance the anti-carcinogenic activity of the immune system. [18][19][20][21] Since the bacterial properties required for the different applications are clearly distinct, selection of the LAB strain is very important for a more rational use of these organisms. 9) Studies imply that not all immunoregulatory LAB strains are likely to be effective in promoting Th1-type anti-allergy immune responses.…”
mentioning
confidence: 99%
“…Nevertheless, there is growing evidence that probiotics have immunomodulatory properties and that these properties of probiotics are strain-dependent (32)(33)(34)(35)(36)(37)(38)(39)(40)(41) . For example, there is consistent evidence that a number of probiotics enhance natural killer (NK) cell activity in vitro (40)(41)(42)(43) and there is some supportive evidence that this also occurs in vivo (44)(45)(46) . Probiotic strains whose cell walls are resistant to digestion appear to be particularly potent enhancers of NK activity; it is suggested that monocytes phagocytose the probiotic bacteria and the insoluble cell wall components induce the production of IL-12, which augments NK cell activity (38,47) .…”
Section: Probiotics Ageing and Immunitymentioning
confidence: 99%